Electrochemical Corrosion of Magnesium Alloy AZ31 with Additive Lithium - Przondziono J. (Archives of Metallurgy and Materials, 2017)
The purpose of performed tests was evaluation of resistance to electrochemical corrosion of extruded magnesium alloy AZ31 with additive of 4.5% Li. Corrosion tests were performed in 0.01-2.0 M NaCl solutions. Potentiodynamic tests enabled to register polarisation curves. With application of stereoscopic microscope Nikon SMZ745T and electron scanning microscope Hitachi S-4200, the surface of the alloy was observed after immersion tests performed in 1-6 days. Results of performed tests prove explicitly deterioration of corrosion properties of the alloy with the increase of molar concentration of NaCl solution. It can be seen that corrosion process is intensive and that intensity increases with the increase of solution concentration and extension of exposure time.